Agriculture Hedge Funds - Gondell, Grant (My University, 2019)
The concept of managed money as a hedge fund is rapidly changing. At the close of 2017, there was sentiment that the days of easy returns and high compensation for fund managers were gone. More hedge funds closed than opened after 2015. Faced with increased pressure over high fees, lagging returns, increased competition and alternative investment options, from firms such as Vanguard Group, that offer passive investments with quantitative strategies, the ability to attract and retain capital has become increasingly challenging. As a result, the managed money landscape is open to new opportunities for fund managers with unique strategies to earn money. This study compares and contrasts characteristics of successful hedge funds. Identifying characteristics from those funds will assist in determining if there is an opportunity for creating alternative investment portfolios. Additionally, researching investment fund failures provides support to evaluate alternative investment portfolios. The purpose of this research is to evaluate the possibility and potential success of starting an agricultural hedge fund while identifying and testing a trading strategy that can generate a consistent return.
Keywords: Hedge Fund; Agriculture; Risk Analysis; Trading Strategy